TINJAUAN HUKUM POSITIF DAN FIQIH HAK ATAS KEPEMILIKAN TANAH - Shohib Muslim; Hairus; Rokiyah (Qolamuna : Jurnal Studi Islam, 2021)
This article discusses land ownership rights in fiqh and positive law in Indonesia. The results of the study conclude that. Based on the results of the analysis, it can be concluded: first, UUPA No. 5/1960 explained the control over the earth, water, space, including the natural resources contained therein by the state. Based on the right of control on land, property rights can be given/controlled by individuals (people) and legal entities that have the authority to use the land according to the type of land rights. Second, in the perspective of fiqh, the land is limited and cannot be developed, such as other factors of production, then the regulation needs to be precisely regulated. Regulations regarding ownership and other rights to land, such as usufructuary rights, building use rights, and so on, become very important. Keywords; Rights, land ownership, fiqh, positive law